1984
DOI: 10.1038/307693a0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-activated potassium channels and their role in secretion

Abstract: Single-channel recording by the patch-clamp technique has now characterized three kinds of membrane potassium channels activated by intracellular calcium ions in animal cells. These play a crucial part in the regulation of membrane potential and of secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
290
1

Year Published

1985
1985
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 657 publications
(311 citation statements)
references
References 65 publications
20
290
1
Order By: Relevance
“…In view of this it is curious that isoprenaline failed to increase 86Rb efflux from guinea-pig trachealis. Airways smooth muscle may contain several kinds of K+ channel (Inoue et al, 1983) and the K+ channels of excitable cells may not all be permeable to 86Rb (Petersen & Maruyama, 1984). This raises the possibility that isoprenaline opens trachealis K+-channels which are impermeable to 86Rb.…”
Section: Resultsmentioning
confidence: 99%
“…In view of this it is curious that isoprenaline failed to increase 86Rb efflux from guinea-pig trachealis. Airways smooth muscle may contain several kinds of K+ channel (Inoue et al, 1983) and the K+ channels of excitable cells may not all be permeable to 86Rb (Petersen & Maruyama, 1984). This raises the possibility that isoprenaline opens trachealis K+-channels which are impermeable to 86Rb.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that basolateral K ϩ channels, which can be blocked by Ba 2ϩ , make an important contribution to the maintenance of membrane potential (V m ) in epithelial cells (32), and such channels could thus play an important role in epithelial Na ϩ transport by maintaining the driving force for Na ϩ entry (25,27). The present study, in common with earlier data (27), showed clearly that Ba 2ϩ abolishes the response to isoprenaline, but, in our hands, this cation caused only transient inhibition of basal I sc .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be interesting to relate actions of these sensory neuropeptides and chemical mediators to the modulation of K ‫ם‬ and Cl ‫מ‬ conductances in dental pulp cells. As described in a wide variety of cells, ion channels can be involved in the signal codes for proliferation, secretion of extracellular matrix proteins and cell differentiation 8,11,20,22) as well as the intercellular electrical/chemical communications through gap junctions 2,3,8,9,19,21,24,28) . The K ‫ם‬ and Cl ‫מ‬ channels expressed in dental pulp cells are most likely responsible for cellular functions underlying dental pulp metabolisms.…”
Section: Discussionmentioning
confidence: 99%